2020
DOI: 10.1002/cti2.1202
|View full text |Cite
|
Sign up to set email alerts
|

Use of human splenocytes in an innovative humanised mouse model for prediction of immunotherapy‐induced cytokine release syndrome

Abstract: Objectives Humanised mice have emerged as valuable models for pre‐clinical testing of the safety and efficacy of immunotherapies. Given the variety of models available, selection of the most appropriate humanised mouse model is critical in study design. Here, we aimed to develop a model for predicting cytokine release syndrome (CRS) while minimising graft‐ versus ‐host disease (GvHD). Methods To overcome donor‐induced variation, we directly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
(180 reference statements)
0
18
0
Order By: Relevance
“…Following myeloablation by low dose total body irradiation or busulfan treatment, 4 to 7 weeks-old mice are intravenously injected with 60 – 100 x 10 3 human CB-derived CD34 + HSCs, which will home to the bone marrow ( 12 , 17 ). Alternatively, intrahepatic injection of HSCs can be performed in newborn mice ( 27 ).…”
Section: Humanization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following myeloablation by low dose total body irradiation or busulfan treatment, 4 to 7 weeks-old mice are intravenously injected with 60 – 100 x 10 3 human CB-derived CD34 + HSCs, which will home to the bone marrow ( 12 , 17 ). Alternatively, intrahepatic injection of HSCs can be performed in newborn mice ( 27 ).…”
Section: Humanization Methodsmentioning
confidence: 99%
“…Human CD45 + cells may be detected in the mouse peripheral blood on week 4, and they reach a plateau on weeks 8 to 10. The main reconstituted human population is the hCD19 + B cells while hCD3 + T cell count remains rather low until weeks 10 - 12 to reach their maximum level at weeks 18 to 20. hCD14 + monocytes can be found at a density of 1 – 5% of hCD45 + cells ( 12 , 28 ). When human pro-T cells migrate to the mouse thymus, positive and negative selection allows for the establishment of a mature T cell population unable to attack murine tissue ( 29 ) ( Figure 1B ).…”
Section: Humanization Methodsmentioning
confidence: 99%
“…Novel strains of immunocompromised mice have been developed to delay GvHD through elimination of major histocompatibility complex (MHC) class I and/or II expression [92][93][94]. Most recently, the use of NSG-(K b D b ) null (IA) null (NSG-dKO) mice, deficient in murine MHC I and II, was shown to significantly delay GvHD post PBMC engraftment (up to 125 days) [93] and SPMC engraftment (up to 140 days) [77]. This improved survival is consistent with xenoreactivity being predominantly driven by murine MHC class I and II molecules.…”
Section: Modeling Longitudinal Immunotherapy Responsesmentioning
confidence: 99%
“…They demonstrated that SPMCs can be used for the successful engraftment of immune cells, showing hCD45 + ve cells in the circulating blood, spleen and liver of the mice. Similar to the hu-PBL model, engrafted immune cells from SPMC reconstitution was mostly T-cells with an effector memory phenotype [ 77 ].…”
Section: Autologous Io Models: Limitations and Innovationsmentioning
confidence: 99%
“…They reported that NSG mice reconstituted with PBMC‐and SPMC better predicted OKT3‐mediated CRS. The SPMC model allows generation of large experimental groups while NSG‐dKO mice are able to mitigate the limitation of early GVHD 85 …”
Section: Pre‐clinical Experiences Of Humanized Micementioning
confidence: 99%